Progresive Muscle Relaxation sebagai Terapi Keperawatan Non-Farmakologis untuk Ketidakstabilan Kadar Glukosa Darah pada Pasien Diabetes Tipe 2: Studi Kasus - Novita Surya Putri; Andrik Hermanto; Meira Safira Salsabila; Atik Pramesti Wilujeng; Riyan Dwi Prasetyawan; Tria Anisa Firmanti; Sholihin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Diabetes mellitus (DM) is a metabolic disease characterized by unstable blood glucose. Unstable blood glucose levels are influenced by psychological and physiological stress, which triggers the secretion of stress hormones, thus worsening glycemic control. Non-pharmacological therapy using relaxation techniques is needed to reduce stress, including progressive muscle relaxation. Objective: The aim of this study was to implementing progressive muscle relaxation as a non-pharmacological nursing therapy for blood glucose level instability in type 2 diabetes patients: a case study. Methods: The research method used is a case study; the nursing problem in DM clients is Unstable blood glucose levels. Treatment that can be carried out for DM clients in dealing with nursing problems of unstable blood glucose levels is PMR therapy. The participants selected were two clients with blood glucose levels ≥200 mg/dl (Hyperglycemia). The research used interview techniques, observation, physical examination, documentation studies, and questionnaires. The assessment format used is the Medical Surgical Nursing format. Results: Progressive Muscle Relaxation (PMR) is given once daily for three consecutive days, with the intervention lasting 15–20 minutes. PMR therapy can effectively reduce blood glucose levels within three days. Participants experienced a decrease in blood glucose levels by an average of 1-24 mg/dl. Conclusion: The PMR relaxation technique affects the neuroendocrine system by reducing the response to stres. When the body is in a relaxed state, the dominance of the parasympathetic system increases, which is able to suppress the secretion of stress hormones and increase insulin sensitivity, thus having a positive impact on regulating blood glucose levels.